General public awareness in life insurance / Asyiera Mohd Yuzanai ... [et al.] - Mohd Yuzanai, Asyiera; Zulkurnain, Zulkurnain; Zainurin, Izz Zafirah; Mohd Shukri, Nur Syaida; Ab Hasan, Zunaidah (Universiti Teknologi MARA, Kedah, 2023)
The approach we take focuses on how to offer an accessible and engaging way to draw individuals with various learning styles, ensuring that they are given the knowledge in the simplest way possible. We discovered that society is less concerned with purchasing life insurance because additional study is required before they can determine which insurance is most suitable for them. People consequently fail to recognize the significance of insurance in their life and how it might safeguard them in the future. In another development, society searches for insurance companies after a calamity has already struck, even though insurance may reduce the financial burden of living. The projects' goals include educating the public about insurance, especially the younger generation, protecting one's finances from unforeseen life events (to avoid losses), and finally, lowering financial uncertainty and making unforeseen losses manageable. We have made our product unique from other recently developed teaching tools to secure its success. We use animation to help with retention since visual learning is one of the learning methods that helps in understanding. We also included a QR code to make it easier for consumers to find out more about insurance. Our products have numerous advantages for society. A couple of these can spark a young person's curiosity about insurance and encourage them to study more about it. The puzzle does not need to be paid for by society. Furthermore, our product takes less time. The target market for this product is teenagers and students. To get the insurance business interested in our puzzles, we took the initiative to propose this product to them for commercialization on their website. Making insurance information easier to access and comprehend will help grab their attention.